الدور التنموي للوساطة المالية في ليبيا خلال الفترة 1980-2023 (Comprehensive Journal of Science, 2026)
This study examines the impact of financial intermediation on economic growth in Libya over the period 1980-2023, using Autoregressive Distribution Lag (ARDL) method and the Granger causality test. The analysis relies on indicators of financial development, including the ratio of money stubbly to GDP, total credit to GDP, and total deposits to GDP. In addition, the growth rate of nominal GDP is employed as a proxy for economic growth. The result reveals the existence of a long-run equilibrium relationship between financial intermediation variables and economic growth. Furthermore, the findings indicate a unidirectional causal relationship running from financial intermediation variables to economic growth. The study emphasizes the importance of developing the financial sector as a key drive for promoting sustainable economic growth in Libya.
Keywords: Financial intermediation, economic growth.